Kecerdasan Religius Umat Islam di Desa Betteng Deata, Kec. Gandangbatu Sillanan, Kab. Tana Toraja, Sulawesi Selatan - Surono, Surono; Husin, Muhammad Said; Musfiroh, Imroh Atul (ISLAMIKA, 2024)
Religious intelligence is an intelligence that can be used to face and solve problems of meaning and value. It can be interpreted that this intelligence can place a person's behavior and life in a broader meaning. The diversity of Muslims is characterized by the ability of the Muslim minority community to carry out social activities with non-Muslim communities, such as the inauguration of traditional houses and other social activities in Betteng Deata village. The aim of this research is to determine religious intelligence, forms of religious intelligence and factors that influence religious intelligence in Islamic communities in Betteng Deata Village, Kec. Gandangbatu Sillanan, Kab. Tana Toraja, South Sulawesi. In this research, a qualitative descriptive research method was used by selecting the problem under study, namely the religious intelligence of Muslims in Betteng Deata Village, Kec. Gandangbatu Sillanan District. Tana Toraja, South Sulawesi. The results of this research found religious intelligence in the form of the ability of Muslims to provide a good example to the general public, such as in selecting village leaders, the ability to respect differences in beliefs, such as during the celebration of religious holidays, the ability to resolve problems, such as differences of opinion between groups, the ability to create religious harmony, such as in social activities. Apart from that, several forms of religious intelligence among Muslims were found, such as eradicating illiteracy in the Koran (Dirosa), opening Kindergartens/TPAs, as well as monthly recitations from house to house. As well as various factors that influence religious intelligence, namely environmental factors and congenital factors.